Chemically Fueled Block Copolymer Self‐Assembly into Transient Nanoreactors. Issue 5 (1st April 2021) - Würbser, Michaela A.; Schwarz, Patrick S.; Heckel, Jonas; Bergmann, Alexander M.; Walther, Andreas; Boekhoven, Job
Abstract: In chemically fueled supramolecular materials, molecular self‐assembly is coupled to a fuel‐driven chemical reaction cycle. The fuel‐dependence makes the material dynamic and endows it with exciting properties like adaptivity and autonomy. In contrast to the large work on the self‐assembly of small molecules, we herein designed a diblock copolymer, which self‐assembles into transient micelles when coupled to a fuel‐driven chemical reaction cycle. Moreover, we used these transient block copolymer micelles to locally increase the concentration of hydrophobic reagents and thereby function as a transient nanoreactor. Abstract : Reaction center : The self‐assembly of block‐copolymer micelles is coupled to a fuel‐driven chemical reaction cycle. In their finite lifetime, the micelles are able to locally increase the concentration of reagents for a Diels‐Alder reaction and drastically accelerate its rate. Thus, the kinetically controlled block copolymer micelles function as temporary nanoreactor.